Assessing changes to the fecal microbiota in dogs undergoing elective orthopedic surgery: A preliminary investigation - Allison J. Collier; Diego E. Gomez; Melissa A. MacIver; Adronie Verbrugghe; J. Scott Weese; Shauna L. Blois (PLoS ONE, 2025)
Background Studies assessing the impact of surgery on the canine gut microbiota are limited. This study assessed the fecal microbiota before and up to 3 months after elective orthopedic surgery. Methods Fourteen client-owned dogs >1 year of age undergoing elective orthopedic surgery were recruited. Dogs received perioperative antibiotics only (perioperative cefazolin, n = 7) or were discharged with oral cephalexin following surgery for 5–7 days (n = 7) in conjunction with perioperative antibiotics. Fecal samples were collected at baseline and at recheck 1 (13–50 days post-operatively) and recheck 2 (55–90 days post-operatively). The fecal microbiota was analyzed using 16S amplicon sequencing. Alpha diversity was assessed with the Sobs Index, Shannon Diversity Index, and Inverse Simpson Index, whereas beta diversity was assessed with the Bray-Curtis Index and Jaccard Index. Results In the perioperative and post-operative antibiotic groups, the Inverse Simpson and Shannon Diversity Index differed between baseline and recheck 1 (p < 0.05), baseline and recheck 2 (p < 0.05), but not between recheck 1 and recheck 2 (p > 0.05). The Sobs Index was only significantly different between baseline and recheck 1 (p = 0.02) in both groups. The Bray-Curtis and Jaccard Index were significantly different at rechecks 1 and 2 compared to baseline (p > 0.05) in the post-operative antibiotic group but not in dogs that received only perioperative antibiotics. Both the Bray Curtis and Jaccard Index were significantly different between the antibiotic prescription types (p = 0.001) although measures of alpha diversity were not (p > 0.05). Conclusions Alterations in community structure, richness, and diversity were identified in dogs undergoing elective orthopedic surgery, with many changes persisting at least 2–3 months post-operatively in dogs receiving perioperative and/or post-operative antibiotics.